Analisis Praktik Pembelajaran Bilingual melalui Video: Kajian Metode, Strategi, dan Media Pembelajaran di Sekolah Dasar - oktaviani, diah ayu; Rochim, Muhammad Alifur; Azizah, Windiarti Nur; Manunggal, Syaharani Alfa; Sari, Mutia Kurnia; Widagdo, Arif (Peneliti.net, 2025)
This study aims to examine the methods, strategies, and media of bilingual learning applied at the elementary school level. The study was conducted through a literature review approach by collecting data from various theoretical sources and descriptive analysis of bilingual learning videos on the YouTube platform. The results of the study indicate that bilingual learning has the potential to improve linguistic competence, develop cognitive skills, and encourage students' academic achievement. Effective learning models include an integrated thematic approach, the application of structured language rotation, the use of interactive digital media, and the integration of cultural values ​​from both languages. Learning evaluation is carried out through formative and summative assessments such as portfolios, classroom observations, and competency-based tests. The obstacles faced include the limited number of bilingual teachers, the lack of relevant teaching materials, and differences in students' language proficiency levels. The solutions needed include ongoing teacher training, the development of an adaptive bilingual curriculum, and collaboration between stakeholders to support the implementation of optimal bilingual learning.